2023
DOI: 10.1149/1945-7111/acd359
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Assisted Etching of n-Type and p-Type Silicon Using Patterned Platinum Films: Spatial Distribution of Mesoporous Layer and Open Circuit Potential of Silicon

Abstract: Platinum (Pt) is one of the interesting catalysts in metal-assisted etching (metal-assisted chemical etching) of silicon (Si). The Pt-assisted etching induces not only the dissolution of Si under the Pt catalysts but also the formation of mesoporous layer on the Si surface away from them. In this work, we etched n-Si and p-Si by using patterned Pt films with a diameter of 5 μm and an interval of 50 μm. For both cases, the Si surface under the Pt catalysts was selectively etched and macropores with a diameter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…[1][2][3][4]7,8,10,[22][23][24][25][26][27][28][29][30][31][32] For example, when using platinum (Pt) catalysts, not only straight pores formed by the preferential dissolution of Si beneath the Pt catalysts but also mesopores covering on the entire surface of Si can be obtained. [33][34][35][36][37][38][39][40] However, the formation mechanism of the composite porous structure is not fully understood. We previously demonstrated that a characteristic composite structure (mesoporous layer thickness exceeds straight pore depth) is formed on highly-doped p-Si and the thick mesoporous layer can be attributed to the tunneling effect at the Si/electrolyte interface.…”
mentioning
confidence: 99%
“…[1][2][3][4]7,8,10,[22][23][24][25][26][27][28][29][30][31][32] For example, when using platinum (Pt) catalysts, not only straight pores formed by the preferential dissolution of Si beneath the Pt catalysts but also mesopores covering on the entire surface of Si can be obtained. [33][34][35][36][37][38][39][40] However, the formation mechanism of the composite porous structure is not fully understood. We previously demonstrated that a characteristic composite structure (mesoporous layer thickness exceeds straight pore depth) is formed on highly-doped p-Si and the thick mesoporous layer can be attributed to the tunneling effect at the Si/electrolyte interface.…”
mentioning
confidence: 99%